Design and Build BTS R2 Information System ("R2 Service Ticket Booking") Web-Based: Rancang Bangun Sistem Informasi BTS R2 ("Booking Tiket Servis R2") Berbasis Web - Sukma, Yudya Hastriawan; Astutik, Ika Ratna Indra (Indonesian Journal of Innovation Studies, 2022)
Technology is currently developing rapidly, especially in the light vehicle automotive sector. This increasingly rapid competition requires business people to maximize their business performance in order to compete in the modern market. Marno Motor Workshop is an MSME engaged in the repair and maintenance of two-wheeled vehicles or motorcycles. The system used in the Marno Motor workshop is still manual. Therefore, in this final report, the author provides suggestions in the form of booking a web-based computerized motorcycle service. Where the system design uses Unifeld Modeling Language (UML) with Hypertext Preprocessor (PHP) programming language, MYSQL database, and uses the Waterfall system development method and uses a system testing method called the Black Box Testing Method. The result of this research is the establishment of an information system for BTS R2 (Wheel Ticket Ordering Service 2) Web-Based at Marno Motor Workshop. With the establishment of this system, it is hoped that it will make it easier for customers to service motorbikes.